Mitigation of Food Crisis and Increasing Productivity of Rice Fields for Communities Around the Taman Asoka Asri Housing Amid the Covid-19 Pandemic - Muhdi, Muhdi; Hanafiah, Diana Sofia; Onrizal; Samsuri; Ridwanti, Batubara (Talenta Publisher, 2021)
Currently, the global economy is shaken by the Covid-19 pandemic. Based on the results of the preliminary study at the partner's location, it has economic limitations, including the availability of food supply which has an impact on non-productive communities, including farmers and tenant farmers around Taman Asoka Asri Housing, Tanjung Selamet, Medan Tuntungan, Medan, North Sumatra. All activities that will be carried out by the USU PPM proposing team will of course follow and pay attention to the Covid-19 prevention protocol. The implementation of this community service is carried out in the vicinity of the Taman Asoka Asri Housing, so the activity plan that will be carried out is the use of rice fields for farmers and cultivators in the environment around the Taman Asoka Asri Housing. The area of ​​paddy rice fields managed by smallholders around the Taman Asoka Asri Complex, Tanjung Selamet, Medan Tuntung, Medan an average of 2,725 m2 (0.2725 ha). Rice field management areas that have been successfully managed by partners have become productive areas that can increase income and profits for smallholders.